Investigation of the Influence of Computer Algebra System Supported Teaching from Procedural-Conceptual Competencies: The Case of Integrals - (:unkn) unknown (HACETTEPE UNIV, 2016)
In this study, effects of a calculus class, teaching content of which, was organized according to reform approach and in which CAS support was benefited on procedural and conceptual competencies for integral were compared with traditional teaching process. This study was designed according to multiple case study since CAS supported and traditional teaching cases are assessed with a holistic approach over learning domain components together with the competencies within procedural-conceptual dimension. Working group of the study consisted of 84 undergraduates registered to Calculus I in mathematics education department of a state university. 6-week application process was completed by following traditional teaching (n= 42) in one of the application groups constituted by unbiased assignment among the students in the workgroup and CAS supported teaching (n= 42) pattern in the other. Test and interview techniques were employed for evaluation of the outputs of teaching process. The findings demonstrated that the undergraduates in the CAS group had higher competency in both procedural and conceptual dimensions when compared to those in the traditional group. It was observed that the difference between the groups was more prominent in the competency related to conceptual dimension. Additionally, it was observed that both groups had higher procedural competencies when compared to conceptual competencies. It was observed that CAS group had higher competencies in limit-integral relation, geometrical interpretation of integral and learning domains of integral applications, while traditional group had higher competencies in derivative-integral relation and learning domains of integration calculation.
Keywords: computer algebra system; procedural-conceptual competency; integral topic